Highly Selective Recovery of Pt(IV) from HCl Solutions by Precipitation Using 1,4-Bis(aminomethyl)cyclohexane as a Precipitating Agent - Kazuya Matsumoto; Ryu Sakamoto; Yoshiya Sakuta; Ryota Aoki; Hiroshi Katagiri; Mitsutoshi Jikei (Metals)
To ensure the sustainable use of limited resources, it is essential to establish selective and efficient recycling technologies for platinum group metals (PGMs). This study focused on the selective precipitation-based separation of Pt(IV) from hydrochloric acid (HCl) solutions in the presence of various metal ions, using trans-1,4-bis(aminomethyl)cyclohexane (BACT) as a precipitating agent. By using BACT, we succeeded in the selective separation of Pt(IV) by precipitation from HCl solutions containing Pd(II) and Rh(III). Notably, selective and efficient recovery of Pt(IV) was accomplished across various HCl concentrations, with a small amount of BACT and within a short shaking time. To evaluate the practical applicability of the method, Pt(IV) was recovered and purified from the HCl leachate of spent automotive exhaust gas purification catalysts using BACT. As a result, a high Pt recovery of 95.6% and a high purity of 99.3% were achieved. Although Pt(IV) was recovered as a precipitate containing BACT, it was found that Pt black could be readily obtained by dissolving the precipitate in HCl solution followed by reduction with sodium borohydride. Detailed structural analysis of the Pt(IV)-containing precipitate revealed that it is an ionic crystal composed of [PtCl6]2− and protonated BACT. The selective formation of this ionic crystal in HCl solution, along with its stability under such conditions, is the key to the selective recovery of Pt(IV) using BACT.